Characterization of culturable bacterial endophytes and their capacity to promote plant growth from plants grown using organic or conventional practices - Xia, Ye; DeBolt, Seth; Dreyer, Jamin; Scott, Delia; Williams, Mark A. (Frontiers in Plant Science, 2015)
Plants have a diverse internal microbial biota that has been shown to have an important influence on a range of plant health attributes. Although these endophytes have been found to be widely occurring, few studies have correlated agricultural production practices with endophyte community structure and function. One agricultural system that focuses on preserving and enhancing soil microbial abundance and biodiversity is organic farming, and numerous studies have shown that organically managed system have increased microbial community characteristics. Herein, the diversity and specificity of culturable bacterial endophytes were evaluated in four vegetable crops: corn, tomato, melon and pepper grown under organic or conventional practices. Endophytic bacteria were isolated from surface-sterilized shoot, root and seed tissues and sequence identified. A total of 336 bacterial isolates were identified, and grouped into 32 species and 5 phyla. Among these, 239 isolates were from organically grown plants and 97 from those grown conventionally. Although a diverse range of bacteria were documented, 186 were from the Phylum Firmicutes, representing 55% of all isolates. Using the Shannon diversity index, we observed a gradation of diversity in tissues, with shoots and roots having a similar value, and seeds having the least diversity. Importantly, endophytic microbial species abundance and diversity was significantly higher in the organically grown plants compared to those grown using conventional practices, potentially indicating that organic management practices may increase endophyte presence and diversity. The impact that these endophytes could have on plant growth and yield was evaluated by reintroducing them into tomato plants in a greenhouse environment. Of the bacterial isolates tested, 61% were found to promote tomato plant growth and 50%-64% were shown to enhance biomass accumulation, illustrating their potential agroecosystem application.